Regional integration and the global economy (UN New YorkUS, 2001)
Identifies some of the issues related to the trade aspects of regional integration agreements and their impact on development. Addresses regional monetary issues in the context of regional integration and the global economy. Focuses on issues relating to provisions on international investment within regional integration agreements.
Keywords: REGIONAL INTEGRATION